The genome sequence of the sycamore periphyllus aphid, Periphyllus acericola (Walker, 1848) [version 1; peer review: 2 approved] - Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual female Periphyllus acericola (the sycamore periphyllus aphid; Arthropoda; Insecta; Hemiptera; Aphididae). The genome sequence has a total length of 405.30 megabases. Most of the assembly is scaffolded into 9 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 33.63 kilobases in length. Gene annotation of this assembly on Ensembl identified 21,463 protein-coding genes.